An investigation of the relationship between the self-image of the teacher and the perception of the students based on observed clothing behavior of the teacher - Festin, Rowena M.; Ruiz, Johanna M.; Ynchausti, Natividad S. (1991.)
The study compared the self-image of teachers with the perception of students based on the observed clothing behavior of the teachers. The study was conducted at the University of the Philippines in Diliman, Quezon City. There were 84 respondents; 4 female teachers, 23 male students and 57 female students. A checklist questionnaire was used for gathering data. The questionnaire was composed of 3 parts: 1) the background information of respondents; 2) the impression of students on the physical appearance of the teacher based on clothing behavior; and 3) the sketches of the different types of clothing personalities. The statistical tools that were used were the chi-square test, analysis of variance, and the frequency distribution. Findings of the study showed the following results: - there is no significant difference between the self-image of teachers and the perception of students with the way the teachers dress in relation to age, to what features they try to enhance, and the type of clothing being projected by the teacher. - there is a significant difference between the self-image of teachers and the perception of students of the physical feature she tries to conceal through clothing. - students and teachers had different perceptions. - there is no significant difference in the perceptions of male and female students of the clothing behavior of teachers. However, observations of the researchers revealed that - the athletic type of clothing is the most ideal personality of clothing perceived by the students to be worn by the teachers. - comfort and simplicity are the number one characteristics of clothing both teachers and students consider that should be possessed by the clothing of teachers. These two observations support each other because the athletic personality has, for its major characteristics, the comfort and simplicity students and teachers believe clothing of teachers should possess.
Thesis (BS Clothing Technology)--University of the Philippines Diliman.
Keywords: Teachers -- Clothing -- Philippines; Physical appearance based-bias -- Philippines -- Quezon City